2005
DOI: 10.1364/ol.30.000180
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort-pulse modulation in adiabatically prepared Raman media

Abstract: We demonstrate the efficient modulation of an approximately 100-femtosecond pulse in a Raman medium coherently prepared by nanosecond pulses. Raman sidebands of the ultrashort pulse spanning 360 THz are generated with an efficiency of >5%. We show that the mechanism permitting the sidebands to be generated is the preparation of a significant vibrational coherence in the medium that is robust to disturbance by an intense short pulse. If the observed sidebands were phase compensated, they would form a short trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…For example, if a Raman interaction is probed by a beam that does not lie on the frequency comb defined by the pumping beams (e.g. as in [13]), the multi-field approach will become much more complicated to implement. It will be necessary to define separate arrays for the pump and probe Raman "ladders" of Stokes and anti-Stokes lines, an issue that we avoided in section IV by replacing the pump stage of the process with an initial condition for the polarization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, if a Raman interaction is probed by a beam that does not lie on the frequency comb defined by the pumping beams (e.g. as in [13]), the multi-field approach will become much more complicated to implement. It will be necessary to define separate arrays for the pump and probe Raman "ladders" of Stokes and anti-Stokes lines, an issue that we avoided in section IV by replacing the pump stage of the process with an initial condition for the polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Since in the experiments of [1,2,3,4,13] the emphasis was on a single Raman transition, a simple Bloch model is clearly appropriate, and indeed our approximations differ little from those of other theoretical approaches (such at that of HPB).…”
Section: Wbrammentioning
confidence: 99%
See 1 more Smart Citation
“…The idea is that the modulator can be used to efficiently generate sidebands on a femtosecond oscillator to produce a broad spectrum with a large number of spectral components. This scheme was first suggested by Kien et al [53], and was later experimentally demonstrated with Q-switched pulsed lasers by Marangos and colleagues [54][55][56]. Consider a broadband laser with power spectral density F (ν).…”
Section: Modulation Of a Femtosecond Ti:sapphire Oscillatormentioning
confidence: 99%
“…This approach requires high energy pulses, of duration less than the molecular oscillation period. In contrast, adiabatic techniques drive molecular motion at the beat frequency of applied pump and Stokes fields, resulting in broadband combs of Raman sidebands produced by phase modulation [8,9]; such sidebands have been used to synthesize long trains of few-fs pulses [10]. In this technique the length of the fs pulses within the train varies from shot to shot.…”
mentioning
confidence: 99%